Analisis Efisiensi Rantai Pemasaran Bawang Merah di Kota Banda Aceh dan Aceh Besar - Wiena Alizza; Agustina Arida; Fajri Jakfar (Jurnal Penelitian Agrisamudra, 2019)
Shallots price in Banda Aceh and Aceh Besar city have a fluctuation. The household complained when the price was so expensive and the farmers complained when the price so cheap. The aim of this research to know marketing efficiency, marketing channel type, marketing margin, marketing profit of shallots in Banda Aceh and Aceh Besar city. This research used survey method and anlysis method used descriptive method, margin analysis and marketing efficiency. The result show that shallots marketing channel involve farmer, collector, retailer and consumer; shallots marketing margin in Ulee Kareng market was Rp.1.975/kg, in Peunayong market was Rp.4.950/kg, and in Lambaro market was Rp. 2.625/kg; shallots marketing efficiency in Ulee Kareng market was 10,46% and in Peunayong market was 19,26 %, meanwhile in Lambaro market was 17,26 %.